Edukasi Kesehatan Ibu Hamil Dan Optimalisasi Konsumsi Tablet Multivitamin Di Wilayah Kerja Sukorejo - Rahmawaty Hasan; Fauzah Cholashotul I; Ismayani (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The fulfillment of nutrition for pregnant women is an important factor in reducing the incidence of maternal mortality. Problems related to the low coverage of supplementation with Fe and folic acid are caused by misunderstandings regarding supplementation and non-compliance of pregnant women in consuming multivitamin tablets. The community service aims to educate the health quality of pregnant women under working area of midwife in Sukorejo, Situbondo. The implementation consists of: (a) health control of pregnant women by checking hemoglobin; (b) education given directly by the presenters; (c) administration of Fe and folic acid tablets. At the end of activities, the questionnaire was given again to measure the level of understanding of partners regarding the material that has been explained. The results showed that there was an increase in the knowledge of pregnant women as partner regarding the importance of consuming multivitamin tablets, namely Fe and folic acid tablets in maintaining health during pregnancy. Prior to being given education, partners had a low level of knowledge (100%). After the implementation of education, there was an increase in partner knowledge, namely good by 66%, sufficient 23% and less than 11% to partner problems in the form of the importance of taking multivitamin tablets.